PASCA NEW NORMAL: PERUBAHAN SOSIAL-EKONOMI PADA GAYA HIDUP MASYARAKAT (PERSPEKTIF SOSIOLOGI) - Adawiyah, Robiatul; Luayyin, Reza Hilmy; Pertiwi, Fia Ayuning (JSE: Jurnal Sharia Economica, 2023)
The Covid-19 pandemic has left considerable social changes, especially after entering the post-new normal era. Business transformation reaches out to innovation in changing lifestyles reduce physical contact with the community, especially in the marketplace sector. This study uses qualitative research in analyzing social changes in people’s lifestyles after Covid. The results of the research show that 1) Increased Health Awareness. 2) Change of Way of Working 3) Distance Education. 4) Use of Technology and the Internet in general has increased significantly. 5) Changes in Consumption Patterns 6) Mental Health Crisis 7) Concern for Social Vulnerability 8) Changes in Social Habits. The lifestyle of people after the new normal era is that people become more aware of their health. And also flexible working models (Hybrid working). Awareness of environmental issues will probably continue to grow.   And concern for social vulnerability is high. Social change due to technological disruption refers to the significant impacts that occur in society as a result of technological developments that disrupt or change the traditional ways people work, communicate and live. Among them are the resulting digital divide, the way people spend their leisure time and establish relationships with friends and family. Social change after the new normal according to Talcott Parson is not only in the health sector but also in the lifestyle of people who are described as increasingly consumptive. The current changes are in accordance with the theory of structural functionalism in this case in accordance with the theory of adaptation, goal attainment, integration, and latency (AGIL). Socio-economic changes in society according to Auguste Comte, the characteristics of social improvement are the increasing welfare of society.